2020
DOI: 10.1542/peds.2020-0782
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Modified qSOFA Score for Predicting Critical Care Admission in Febrile Children

Abstract: BACKGROUND AND OBJECTIVES: The identification of life-threatening infection in febrile children presenting to the emergency department (ED) remains difficult. The quick Sequential Organ Failure Assessment (qSOFA) was only derived for adult populations, implying an urgent need for pediatric scores. We developed and validated a novel, adapted qSOFA score (Liverpool quick Sequential Organ Failure Assessment [LqSOFA]) and compared its performance with qSOFA, Pediatric Early Warning Score (PEWS), and National Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…We have previously developed such a score, the Liverpool quick Sequential Organ Failure Assessment (LqSOFA) and demonstrated its ability to identify those children at risk of poorer outcomes within a febrile ED cohort. 27 Compared with the AH PEWS, the LqSOFA was less discriminative (AUC 0.93 vs 0.81). 27 However, the LqSOFA has the advantage of using fewer parameters (four vs eight), which are measured easily and consistently, while still achieving good discrimination.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We have previously developed such a score, the Liverpool quick Sequential Organ Failure Assessment (LqSOFA) and demonstrated its ability to identify those children at risk of poorer outcomes within a febrile ED cohort. 27 Compared with the AH PEWS, the LqSOFA was less discriminative (AUC 0.93 vs 0.81). 27 However, the LqSOFA has the advantage of using fewer parameters (four vs eight), which are measured easily and consistently, while still achieving good discrimination.…”
Section: Discussionmentioning
confidence: 89%
“… 27 Compared with the AH PEWS, the LqSOFA was less discriminative (AUC 0.93 vs 0.81). 27 However, the LqSOFA has the advantage of using fewer parameters (four vs eight), which are measured easily and consistently, while still achieving good discrimination. This means it may be ideally suited for settings where BP measurement is inconsistent or impossible, such as prehospital, and resource-poor settings, but the LqSOFA requires further validation in these settings.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Physiologically based scores have been developed for the early recognition of disease severity in children including scores as quick Sequential Organ Failure Assessment (qSOFA), quick Paediatric Logistic Organ Dysfunction-2 (qPELOD-2) and Liverpool qSOFA (LqSOFA). [34][35][36][37] In previous ED studies, these scores showed high specificity but low sensitivity for serious illness. 36 37 LqSOFA is based on heart rate and capillary refill time as haemodynamic parameters, whereas qSOFA and qPELOD-2 both require BP measurement.…”
Section: Original Researchmentioning
confidence: 82%
“…Besides the prognostic value of CRP after trauma, increased CRP levels in febrile children in the emergency department should also initiate further infection diagnostics such as blood culture and smear tests. Furthermore, the Pediatric Early Warning Score (PEWS) and National Institute for Health and Care Excellence (NICE) or the Liverpool quick Sequential Organ Failure Assessment (LqSOFA) (25) are applied in children with acute febrile illness in the pediatric emergency department in order to identify life-threatening infection.…”
Section: Acute Systemic Inflammatory Markersmentioning
confidence: 99%